Coal Fuel Efficiency with Mixed Palm Shell Biomass for Steam Power Plant - Hamzah, Eteruddin; Muhammad, Ridwan; Monice, Monice; Zulfahri, Zulfahri; Yanuar Z., Arief; Fathimah, Hasanti (2021)
The accumulation of coal-based fuels is depleting and to obtain coal fuel requires a great amount of money, as a corollary, measures must be taken to reduce the usage of this fuel. PT. Pembangkit Jawa Bali (PJB) is currently investigating the co-firing technique by using oil palm shell biomass waste as a combination coal fuel with a proportion of 95% coal and 5% palm shell, the efficiency results will be compared to 100% of coal fuel. In this research, the Mathcad program and the Professional Simulator 8 were employed, the specific fuel consumption (SFC) technique is used to determine the efficiency of production expenses, as well as the direct and indirect methods to calculate the boiler efficiency. The results reveal that 4.09 IDR/kWh reduction in primary energy expenses could be achieved (0.65%). Co-firing fuel will undoubtedly have a significant impact on the boiler's performance, therefore when using 100% of coal as a fuel, the boiler efficiency value is 63.38% (Direct Method), while using the Indirect Method will produce up to 82.24%, respectively. However, when using co-firing fuel with 95% of coal and 5% of palm shell (Direct Method), the boiler efficiency value is 63.92%, and 83.71% when using the Indirect Method.